Perceptions held by healthcare professionals concerning organ donation after circulatory death in an Australian intensive care unit without a local thoracic transplant service: A descriptive exploratory study. Issue 4 (July 2022) - Milross, Luke; O'Donnell, Thomas; Bucknall, Tracey; Pilcher, David; Poole, Alexis; Reddi, Benjamin; Ihle, Joshua
Abstract: Background and objective: Organ donation rates continue to be low in Australia compared with demand. Donation after circulatory death (DCD) has been an important strategy to increase donation rates, facilitated by advances in cardiopulmonary support in intensive care units (ICUs). However, DCD may harbour greater logistical challenges and unfavourable perceptions amongst some ICU healthcare professionals. The aim of this study was to evaluate and understand DCD perceptions at an Australian tertiary hospital. Methods: This descriptive exploratory study was conducted at an Australian tertiary hospital. Participants were recruited voluntarily for interview via email and word-of-mouth through the hospital's ICU network. The study used a mixed-methods approach; five close-ended questions were included in the form of Likert scales followed by a semistructured interview with open-ended questions designed to understand participants' perceptions of DCD. Interviews were recorded, transcribed, and thematically analysed. Results: Sixteen participants were interviewed including eight intensive care doctors, four donation specialist nursing coordinators (DSNCs), and four bedside nurses. Likert responses demonstrated clinicians' support for both DCD and donation after brain death (DBD). Thematic analysis of the transcripts yielded three overarching themes including 'Contextual and environmental influences on DCD decision-making', 'Personal difficulties faced by clinicians in DCD decision-making', and 'Family influences on DCD decision-making'. Significant geographical separation between donation and organ retrieval teams, incurring significant resource utilisation, impacted the donation team's decision-making around DCD, as did a perceived disruption of ICU care to facilitate donation especially for cases where successful DCD was identified to be unlikely. Conclusions: Overall, DCD was as acceptable to participants as DBD. However, the geographical separation of this centre meant that logistical barriers potentially impacted the DCD process. Open lines of communication with transplant centres, local resourcing, and a culture of education, experience, and leadership may facilitate the DCD programs where distant retrieval is commonplace.